Cell wall mannan of Candida krusei mediates dendritic cell apoptosis and orchestrates Th17 polarization via TLR-2/MyD88-dependent pathway. Issue 1 (December 2018) - Nguyen, Thu; Padungros, Panuwat; Wongsrisupphakul, Panachai; Sa-Ard-Iam, Noppadol; Mahanonda, Rangsini; Matangkasombut, Oranart; Choo, Min-Kyung; Ritprajak, Patcharee
Abstract Dendritic cells (DCs) abundantly express diverse receptors to recognize mannans in the outer surface ofCandida cell wall, and these interactions dictate the host immune responses that determine disease outcomes.C. krusei prevalence in candidiasis worldwide has increased since this pathogen has developed multidrug resistance. However, little is known how the immune system responds toC. krusei . Particularly, the molecular mechanisms of the interplay betweenC. krusei mannan and DCs remain to be elucidated. We investigated howC. krusei mannan affected DC responses in comparison toC. albicans, C. tropicalis andC. glabrata mannan. Our results showed that onlyC. krusei mannan induced massive cytokine responses in DCs, and led to apoptosis. AlthoughC. krusei mannan-activated DCs underwent apoptosis, they were still capable of initiating Th17 response.C. krusei mannan-mediated DC apoptosis was obligated to the TLR2 and MyD88 pathway. These pathways also controlled Th1/Th17 switching possibly by virtue of the production of the polarizing cytokines IL-12 and IL-6 by theC. krusei mannan activated-DCs. Our study suggests that TLR2 and MyD88 pathway in DCs are dominant forC. krusei mannan recognition, which differs from the previous reports showing a crucial role of C-type lectin receptors inCandida mannan sensing.